Redescription of the female, male, larva and pupa of Sabethes (Sabethoides) glaucodaemon (Dyar & Shannon) (Diptera: Culicidae) and description of the female genitalia - Stein, Marina; Bangher, Debora N.; Neves, Maycon Sebastião Alberto Santos; Alvarez, Carla N. (Zootaxa, 2020)
Sabethes (Sabethoides) glaucodaemon was described for the first time by Dyar & Shannon (1925) based on the adult female. Later, descriptions of the male genitalia and parts of the fourth-instar larva and pupa were published by other authors. No one has described the female genitalia or made a complete description of the larva and pupa. The aim of this study was to redescribe Sa. glaucodaemon in the adult stage, including the male and female genitalia, and the pupa and fourth-instar larva. All stages are illustrated. Distinctions from Sa. (Sbo.) tridentatus are discussed.